2018
DOI: 10.1016/j.adro.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation for malignant glioma: Toward patient selection and defining treatment parameters for salvage

Abstract: PurposeReirradiation for recurrent glioma remains controversial without knowledge of optimal patient selection, dose, fractionation, and normal tissue tolerances. We retrospectively evaluated outcomes and toxicity after conventionally fractionated reirradiation for recurrent high-grade glioma, along with the impact of concurrent chemotherapy.Methods and materialsWe conducted a retrospective review of patients reirradiated for high-grade glioma recurrence between 2007 and 2016 (including patients with initial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…The authors reported that there is no symptomatic persistant brain stem or optic chiasma injury. Grade ≥ 3 late toxicity and radiation necrosis were minimal (less than 5%) [31].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors reported that there is no symptomatic persistant brain stem or optic chiasma injury. Grade ≥ 3 late toxicity and radiation necrosis were minimal (less than 5%) [31].…”
Section: Discussionmentioning
confidence: 95%
“…They observed 60% progression-free survival in 6 months. Another prospective study using 4 -6 cycles temozolamide followed by re-irradiation with 3D conformal radiotherapy (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in recurrent high-grade glioma (grade III and IV). Overall response rate was 20.6% and stable disease was 45% [30].…”
Section: Discussionmentioning
confidence: 99%
“…With conventional fractionated re-RT and median cumulative EQD2 of 99.3 Gy, symptomatic persistent brainstem or optic nerve/chiasm injury was not observed at median cumulative brainstem dose of 76.9 Gy (5.0–108.3 Gy) and optic apparatus dose of 56.0 Gy (4.5–90.9 Gy) [27]. Late CNS toxicity, radiation necrosis, and short-term steroid requirement were not significantly affected by re-RT volume, maximum brainstem/optic structure dose, or time interval of re-RT.…”
Section: Re-rt Alonementioning
confidence: 99%
“…In a study of 118 patients with recurrent malignant glioma (GBL in 74%) treated with CFRT (12.6–54 Gy) with daily dose of 1.8 Gy plus TMZ at 28 months after initial RT, the median OS of 9.6 months was significantly better with dose >41.4 Gy (12.4 vs. 7.1 months) and gross total resection before re-RT (11.9 vs. 7.7 months). The radionecrosis chance was <5% [27]. Another study has found an improvement of median OS by combining re-RT with unspecified chemotherapeutic agents (12.2 vs. 8.2 month) [6].…”
Section: Re-rt With Combined Chemotherapymentioning
confidence: 99%
“…Although historically repeat fractionated radiation for gliomas was considered prohibitively toxic, modern radiation techniques allow for repeat radiation in many cases [8][9][10][11][12][13][14]. Several studies have directly assessed fractionated reirradiation with concomitant bevacizumab and have demonstrated its safety [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%